2009
DOI: 10.1007/s00213-009-1631-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment of astrocytes with therapeutically relevant fluoxetine concentrations enhances cPLA2 expression secondary to 5-HT2B-induced, transactivation-mediated ERK1/2 phosphorylation

Abstract: This demonstration replicates the fluoxetine-induced cPLA(2) upregulation in rat brain shown by Rao et al. (Pharmacogenomics J 6:413-420, 2006) and provides the new information that upregulation (1) occurs in astrocytes, (2) is evoked by stimulation of 5-HT(2B) receptor, and (3) requires transactivation-mediated ERK(1/2) phosphorylation. Similar upregulation of cPLA(2) in intact brain in response to 5-HT(2)-mediated signaling by elevated serotonin levels and/or an SSRI during antidepressant treatment may expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 74 publications
7
26
0
Order By: Relevance
“…Fluoxetine has been reported to increase levels of neurogenesis (Chang, et al, 2010, Li, et al, 2009, Marcussen, et al, 2008, Perera, et al, 2011, Wang, et al, 2011) therefore we examined the effect of fluoxetine in the hippocampus sub-granular zone of the MBP1-hαsyn tg mice. Saline-treated MBP1-hαsyn tg mice display significantly reduced levels of doublecortin, a marker of neuroblasts (Figure 4A, C, E, p<0.05) and PCNA, a marker of proliferating cells in the sub-granular zone of the dentate gyrus (Figure 4F, H, J, p<0.05) in comparison to saline-treated non-tg mice, indicating reduced neurogenesis in the tg mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoxetine has been reported to increase levels of neurogenesis (Chang, et al, 2010, Li, et al, 2009, Marcussen, et al, 2008, Perera, et al, 2011, Wang, et al, 2011) therefore we examined the effect of fluoxetine in the hippocampus sub-granular zone of the MBP1-hαsyn tg mice. Saline-treated MBP1-hαsyn tg mice display significantly reduced levels of doublecortin, a marker of neuroblasts (Figure 4A, C, E, p<0.05) and PCNA, a marker of proliferating cells in the sub-granular zone of the dentate gyrus (Figure 4F, H, J, p<0.05) in comparison to saline-treated non-tg mice, indicating reduced neurogenesis in the tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, a number of studies indicate that fluoxetine treatment may enhance transactivation of serotonin receptors including the 5-HT2B and 5-HT2C receptors (Li, et al, 2009, Li, et al, 2010, Li, et al, 2008) resulting in ERK phosphorylation and activation of the ERK signaling pathway (Li, et al, 2009, Li, et al, 2008, Mercier, et al, 2004). This is consistent with the increased pERK/tERK ratio we observe in the fluoxetine-treated mice and in the in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…But ATP acts via P2Y2 receptors to recruit cPLA 2 by activating both ERK 1/2 and p38 MAPKs and stimulates the release of PGE2 from articular chondrocytes (Berenbaum et al, 2003). In contrast, Li et al (2009) found that chronic fluoxetine treatment upregulates cPLA 2 , without effect on secretory PLA 2 (sPLA 2 ) and intracellular PLA 2 (iPLA 2 ), but this effect could be inhibited by AG1478, an inhibitor of the receptor tyrosine kinase of the epidermal growth factor (EGF) receptor (Levitzki and Gazit, 1995), or by U0126, an inhibitor of ERK 1/2 phosphorylation (Favata et al, 1998). The EGF receptor (EGFR) can be transactivated via G i/o or G q protein-coupled receptors (Peng, 2004;Pierce et al, 2001) and activates two major intracellular signaling pathways, MAP kinases, including ERK, and phosphatidylinositol-3-kinase (PI3K), including Akt.…”
Section: Introductionmentioning
confidence: 93%
“…Astrocytes are among the cells that express calcium-dependent phospholipase 2 (cPLA 2 ) [27, 28], and in the brain in vivo, they may even be enriched in this phospholipase [29–31]. Its activation specifically releases arachidonic acid from the sn -2 position of membrane-bound phospholipid substrate in neural preparations [3235], including glioma cells [36].…”
Section: Effects Of Ssrismentioning
confidence: 99%